A mixed-methods development study of teak wood thematic puzzle media to enhance storytelling skills of 4–5 year old children in early childhood learning settings - Lilis Suryani; Ilis Kandarisah Ilis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study addresses the lack of contextual and developmentally appropriate learning media at KB Arraudoh, where many 4–5-year-old children were found to struggle with story sequencing, coherent expression, and narrative vocabulary. The research aimed to develop thematic teak wood puzzle media while also identifying learning needs, understanding classroom conditions, and examining children’s storytelling progress after implementation. A mixed-methods R&D design using the ADDIE model was applied. Qualitative data from observations, teacher interviews, needs analysis, and documentation were used to analyze children’s characteristics and contextual requirements for media design. Quantitative data were obtained from expert validations and structured assessments in limited field trials. Qualitative findings guided product development, while quantitative results confirmed feasibility and effectiveness. The puzzle media received very high feasibility scores—98.3% (content expert), 98.4% (media expert), and 98.5% (practitioner). Children’s storytelling performance improved significantly, with 85% categorized as Developing as Expected and a 70% increase in achievement after implementation. The integration of qualitative insights and quantitative validation shows that the media effectively supports narrative development through contextual visual cues and structured sequencing. This study contributes a context-based mixed-methods model for early childhood media development and offers practical implications for designing developmentally appropriate storytelling interventions.